2018
DOI: 10.1111/ap.12297
|View full text |Cite
|
Sign up to set email alerts
|

Influences on Psychological Well‐Being and Ill‐Being in Older Women

Abstract: Objectives: To examine factors contributing to psychological well-being and ill-being in older Australian women. Methods: A multi-variable model examining personality traits, life events, medical diagnoses, and cognitive appraisal was tested on 296 women (mean age = 69.13, standard deviation = 10.20) from the Longitudinal Assessment of Women Study using a cross-sectional design. Results: Neuroticism, optimism, and extraversion were associated with both well-being and ill-being, but these relationships were par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 70 publications
1
3
0
Order By: Relevance
“…For example, based on 788 Lithuanians aged above 50 years old, Jurkuvėnas et al [ 27 ] found that neuroticism was negatively related to SWB, whereas extraversion, agreeableness, openness to experience, and conscientiousness were all positively related to SWB. A number of recent studies have also reported similar findings to support the link between the Big Five and SWB among elderly people [ 28 , 29 , 30 , 31 ]. The literature thus indicates that older adults with low levels of neuroticism and high levels of agreeableness, conscientiousness, extraversion, and openness to experience are likely to report higher SWB.…”
Section: Introductionsupporting
confidence: 52%
“…For example, based on 788 Lithuanians aged above 50 years old, Jurkuvėnas et al [ 27 ] found that neuroticism was negatively related to SWB, whereas extraversion, agreeableness, openness to experience, and conscientiousness were all positively related to SWB. A number of recent studies have also reported similar findings to support the link between the Big Five and SWB among elderly people [ 28 , 29 , 30 , 31 ]. The literature thus indicates that older adults with low levels of neuroticism and high levels of agreeableness, conscientiousness, extraversion, and openness to experience are likely to report higher SWB.…”
Section: Introductionsupporting
confidence: 52%
“…The association of negative dysfunctional situation appraisal with well‐being and the occurrence of illness symptoms has also been demonstrated in numerous research studies (e.g. Caron et al, 2012; Tan et al, 2020).…”
Section: Introductionmentioning
confidence: 78%
“…Both domestic and international scholars have developed indicator systems to measure the level of well-being of residents in accordance with the status of ecosystem services in various natural regions [26][27][28][29][30] since the Millennium Ecosystem Assessment report proposed the contribution of ecosystem services to human well-being. A review of related studies elucidated the following: 1 Currently, studies on well-being have developed a variety of indicator systems that cover health well-being [31][32][33][34][35], psychological well-being [36][37][38][39][40][41], social well-being [42][43][44][45][46], and other aspects [47,48]. There has also been some exploration into the perspective of ecological impacts [49][50][51].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the well-being measurement of female groups has primarily focused on the exploration of subjective well-being and influencing factors in qualitative research [52][53][54][55]. systems that cover health well-being [31][32][33][34][35], psychological well-being [36][37][38][39][40][41], social well-being [42][43][44][45][46], and other aspects [47,48]. There has also been some exploration into the perspective of ecological impacts [49][50][51].…”
Section: Introductionmentioning
confidence: 99%